2018
DOI: 10.31186/jenggano.3.2.178-196
|View full text |Cite
|
Sign up to set email alerts
|

Struktur Komunitas Hutan Mangrove Di Pulau Sibu Kota Tidore Kepulauan Provinsi Maluku Utara

Abstract: Ekosistem mangrove di pesisir pulau Sibu mendapatkan berbagai macam tekanan pemanfaatan dari manusia. Hal ini memberikan gambaran bahwa perlu danya informasi ekologi. Stasiun penelitian ditetapkan sebanyak 3 stasiun, yang meliputi bagian utara, selatan dan timur Pulau Sibu. Pengambilan contoh mangrove, di lakukan dengan menggunakan metode transect quadrant dan spot check. Hasil penelitian diperoleh ketebalan hutan mangrove dikawasan Pulau Sibu berdasarkan pengamatan adalah 410 meter (Stasiun I),  321 meter (St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…Another study showed stable mangrove coverage in the most extensive urban area, Tual City in Kei islands, from 1999 to 2019 through satellite imagery analysis (Suyadi et al 2021). Excellent mangrove conditions were also identified in a nearby archipelago in Moluccas Province, in particular Sula Islands, by previous studies based on forest canopy coverage assessments (Akbar et al 2016;Baksir et al 2018). Overall, archipelagic mangroves, especially in eastern Indonesia, were commonly in more health conditions due to a lack of anthropogenic threats compared to the western region (Ilman et al 2016).…”
Section: Mangrove Health Index Distributionmentioning
confidence: 80%
“…Another study showed stable mangrove coverage in the most extensive urban area, Tual City in Kei islands, from 1999 to 2019 through satellite imagery analysis (Suyadi et al 2021). Excellent mangrove conditions were also identified in a nearby archipelago in Moluccas Province, in particular Sula Islands, by previous studies based on forest canopy coverage assessments (Akbar et al 2016;Baksir et al 2018). Overall, archipelagic mangroves, especially in eastern Indonesia, were commonly in more health conditions due to a lack of anthropogenic threats compared to the western region (Ilman et al 2016).…”
Section: Mangrove Health Index Distributionmentioning
confidence: 80%
“…Nilai pH optimal pertumbuhan bakteri berkisar antara 6,5 hingga 7,5 (Fajar et al, 2022). Pertumbuhan mangrove dapat dikatakan baik apabila memiliki nilai pH kisaran 6,5 hingga 8,5 (Baksir et al, 2018). 1,9 x 10 4 8,9 x 10 3 2,9 x 10 4 3,9 x 10 4 3 3,9 x 10 4 3,6 x 10 3 3,5 x 10 4…”
Section: Parameter Kualitas Lingkunganunclassified
“…Indeks Nilai Penting (INP) semai mangrove tertinggi ditemukan pada jenis Ceriops tagal dan Bruguiera gymnorrizha sedangkan jenis Rhizophora mucronata memiliki INP terrendah dibanding jenis lainnya. (Baksir et al, 2018) yang menjadi habitat bagi berbagai organisme laut (Saleky and Merly, 2021;Syahrial et al, 2018) dengan tingkat produktifitas yang tinggi (Dharmawan and Widyastuti, 2017). Selain bagi organisme, ekosistem mangrove juga memberikan manfaat penting bagi manusia (Carugati et al, 2018).…”
unclassified